Cultivating awareness-based well-being: An exploratory study of the use of mindfulness in and as Inclusion in the Early Years - Gonzalez, Barbara (Trinity College (Dublin, Ireland). School of Education, 2022)
Increasing mental well-being challenges for children with additional support needs, their parents and early years educators have been reported in literature, especially during the covid-19 pandemic. The use of mindfulness based practices in early years have emerged in recent years posing a question on how these practices are used and how they could be implemented as a whole-setting approach, as recommended in mindfulness research. This study explores the use of mindfulness based practices for children with additional support needs in the ECCE programme and to support the well-being of their parents and early years educators. It focuses on mindfulness a multifaceted aspect for inclusion and well-being within a multidimensional system framework. This mixed methods study collects quantitative and qualitative data from online surveys and semi-structured interviews. The findings of this study include the views and experiences of early years educators, parents of children with additional support needs and a group of allied professionals consisting of college lecturers, early years and inclusion coaches and mindfulness teachers. They indicate that mindfulness based practices, as an additional tool, can be beneficial for the well-being and inclusion of children with additional support needs and can support the well-being of their parents and early years educators. However, some constraints related to the setting, individual’s context and needs, training, policy and personal and financial commitment are identified. Thus, mixed views on how to incorporate it within Aistear and to facilitate training and parent’s sessions are pointed out. The factors that impacted the well-being of children with additional support needs, their parents and educators are explored. The importance of using mindfulness was associated to children’s anxiety and poor emotional awareness and self-regulation as well as parental and workplace stress due to limited services and heavy workload. The implication for the learning and home environment are also stressed. These findings have some implications for the implementation of mindfulness within Early Years Frameworks, through a conceptualization of mindfulness in early years, policy, and practice. Adequate funding and future research should be undertaken to examine a possible implementation of mindfulness as a whole-setting approach. Keywords: mindfulness, well-being, inclusion, early years, whole-setting approach.
Keywords: Early Intervention; Education